Adenosine and Ischemic Preconditioning - Liang, Bruce T. (1999)
Adenosine is released in large amounts during myocardial ischemia and is capable of exerting potent cardioprotective effects in the heart. Although these observations on adenosine have been known for a long time, how adenosine acts to achieve its anti-ischemic effect remains incompletely understood. However, recent advances on the chemistry and pharmacology of adenosine receptor ligands have provided important and novel information on the function of adenosine receptor subtypes in the cardiovascular system. The development of model systems for the cardiac actions of adenosine has yielded important insights into its mechanism of action and have begun to elucidate the sequence of signalling events from receptor activation to the actual exertion of its cardioprotective effect. The present review will focus on the adenosine receptors that mediate the potent anti-ischemic effect of adenosine, new ligands at the receptors, potential molecular signalling mechanisms downstream of the receptor, mediators for cardioprotection, and possible clinical applications in cardiovascular disorders.